Stop burnout belajar kalkulus: 4 manfaat olahraga sebagai investasi otak mahasiswa tadris matematika - Mufiidah, Amalia (Maliki Interdisciplinary Journal, 2026)
The demanding curriculum of Mathematics Education (Tadris Matematika) students, characterized by intense mental workload from subjects like Real Analysis and Linear Algebra, often leads to chronic stress and academic burnout. This article argues that physical exercise is not a time consumer but a critical investment for cognitive and mental performance in this group. We elaborate on the neurobiological mechanisms (e.g., BDNF activation and cortisol regulation) through which moderate-intensity exercise significantly enhances focus, memory retention, and effective stress management, directly benefiting complex problem-solving abilities. Furthermore, practical, time-efficient solutions, such as 15-minute high-intensity interval training (HIIT), are offered to counter the perceived lack of time. Ultimately, integrating physical activity is proposed as an essential strategy for optimizing academic success and long-term well-being for future mathematics educators.